Sensitivities of lumbar segmental kinematics and functional tissue loads in sagittal bending to design parameters of a ball-in-socket total disc arthroplasty prosthesis. Issue 9 (3rd July 2020) - Zhou, Chaochao; Willing, Ryan
Abstract: Lumbar total disc arthroplasty (TDA) is an attractive option for the treatment of spinal disorders. However, post-operative complications may cause revision surgery. In this study, an in-depth biomechanical analysis was performed to test how sensitive post-operative spinal responses in sagittal bending were to design parameters of a widely used ball-in-socket TDA design. Our simulation results revealed that lowering the intervertebral distraction, posteriorly positioning the implant, or decreasing the radius of curvature of the metal-on-polyethylene bearing surface could result in spinal responses which better matched normal spinal kinematics, but deviated further from the normal spinal tissue load-sharing pattern.